Susceptibility of Sphenarium purpurascens purpurascens (Orthoptera: Pyrgomorphidae) instars to a commercial strain of Metarhizium acridum (Hypocreales: Clavicipitaceae) in Michoacan, Mexico. (2019)
The objective of this study was to evaluate the performance of a commercial strain of the entomopathogenic fungi Metarhizium acridum, on the different instars of the grasshopper pest Sphenarium purpurascens purpurascens, as well as its sporulation via bioassays under laboratory conditions, in Michoacan, Mexico. The most susceptible instars were nymphs one, two and four, with an average survival time of less than 6.91 days. The least susceptible was the adult, with a survival time of 8.36 days. The instars with the highest post mortem sporulation were nymphs one, two and three. A moderate negative association was registered between S. p. purpurascens and the sporulation of M. acridum, in advanced instars (nymph 4 and adult), in which sporulation was lower compared to early instars. All instars showed survival rates below 5 %, so M. acridum can be considered to be a viable option for controlling this pest in the field.